Altered Social Reward and Attention in Anorexia Nervosa - Watson, Karli K.; Werling, Donna M.; Zucker, Nancy; Platt, Michael (Frontiers in Psychology, 2010)
Dysfunctional social reward and social attention are present in a variety of neuropsychiatric disorders including autism, schizophrenia, and social anxiety. Here we show that similar social reward and attention dysfunction are present in anorexia nervosa (AN), a disorder defined by avoidance of food and extreme weight loss. We measured the implicit reward value of social stimuli for female participants with (n = 11) and without (n = 11) AN using an econometric choice task and also tracked gaze patterns during free viewing of images of female faces and bodies. As predicted, the reward value of viewing bodies varied inversely with observed body weight for women with anorexia but not control women, in contrast with their explicit ratings of attractiveness. Surprisingly, women with AN, unlike control women, did not find female faces rewarding and avoided looking at both the face and eyes – independent of observed body weight. These findings suggest comorbid dysfunction in the neural circuits mediating gustatory and social reward in anorexia nervosa.